INCREASE THE ENERGY EFFICIENCY OF IRRIGATION SYSTEM THROUGH WIND-WATER PUMPS (American Journal of Interdisciplinary Research and Development, 2024)
The article discusses the use of renewable energy, which are currently one of the most pressing problems, and achieving energy efficiency by using wind water pumps and energy efficiency in areas where electricity is scarce, windwater pumps can detect the kinetic energy of wind at different speeds and convert them into mechanical energy and apply them to the irrigation system. Additionally, through the kinetic energy of the wind, software has been developed and experimental research has been carried out that allows you to determine the liquid consumption of a desert water pump. The energy efficiency of wind water pumps was estimated through wind speed.